The Teaching Methodology and the Behavior of Ordinary Secondary School Students in Learning Mathematics Subject: A case of selected Ordinary Secondary Schools in Mbeya, Tanzania - Kaula Stephen (MASI Mandiri Edukasi, 2023)
The study investigated the teaching methodology and the behavior of ordinary secondary school students in learning mathematics. This study sought to find behind the scenes why most students in ordinary secondary schools dislike mathematics, which leads to massive failures. To uncover this gap, the study applied a correlation research design. Systematic sampling technique of the interval 50th was used in which 100 respondents were selected; 20 respondents each from 5 selected secondary schools in Mbeya. Data were collected through a questionnaire. Data were analyzed descriptively and speculatively. The survey found that teaching materials/media were effectively implemented. Also, the findings indicate the non-adoption of informal behavior and non-reflection of mathematics teachings to the learner’s natural home environment. Thus, from these discrepancies, the study recommends that mathematics teachers be used to teaching simulation and visual aids/media. It is recommended that mathematics teachers use informal behavior such as courage words, remedial classes, and others for students adapted to mathematics-solving behavior. Lastly, it is suggested that mathematics teachings should be reflexive to students’ real-life environment.